Analysis of managerial roles of secondary school Principals in implementing Competency Based Curriculum (CBC) in Tigania West Sub-county, Meru, Kenya - Mukiri, Jacinta; Njati, Ibuathu Charles; Thuranira, Mercy N. (African Journal of Science, Technology and Social Sciences, 2024)
The study sought to analyze roles of secondary school principal in implementing Competency Based Curriculum (CBC) in Tigania west Sub County. The objectives of the study were; determining leadership skills possessed by principals in secondary schools; establishing availability of resources used by principals; examining how principals involve teachers in monitoring and evaluation; and establishing ways in which principals are involving parents in implementation of competency based curriculum. The study was conducted using descriptive survey design. The target population in the study was 867 participants; 51 principals, 255 HoDs, 510 teachers, and 51 parents in the study area. The sample size of 10 principals, 30 HoDs, 60 teachers and 10 parents were selected using Yamene sample size tables. The test instruments used to collect data were questionnaires, observation checklists and interviews. Quantitative data was analyzed using descriptive statistics while qualitative data was coded analyzed and interpreted using statistical packages for social sciences version 20.0 and summarized into frequency tables, pie charts and bar charts. The response rate was 98.5%. The findings of the study revealed that; principals use democratic and transformational leadership styles which inspire teachers to interact with other teachers; enhance cluster setting of exams, marking and attending workshops together which enhance assessment of learners. In addition, parents are involved in junior secondary school because since CBC had not started in senior Secondary schools. From the findings, the study concluded that, 80% of the secondary school principals are not ready to implement the Competency Based Curriculum due to resource constraints and in-service training of teachers. The study also found that, parents are not much involved on the implementation of Competency Based Curriculum (CBC) in the secondary schools in Tigania West Sub- County in Kenya